Multiple Intelligences-Based Learning Strategies taught by Islamic Religious Education Teachers in Elementary Schools - Asdin, Feby Febrianti; Madi; Ridwan, Muhammad (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2024)
The Multiple Intelligences strategy also lies in its flexibility in accommodating various learning styles of students. With an approach that focuses on diverse intelligences, teachers can design learning that is more interesting and in accordance with the needs of each student. The purpose of this study was to determine the learning strategies based on multiple intelligences taught by Islamic Religious Education teachers to students at SD Negeri 13 Buton. This study used a descriptive qualitative approach with a case study method. This study aims to understand and describe the learning strategies based on Multiple Intelligences applied by Islamic Religious Education (PAI) teachers in Elementary Schools. The results of this study indicate that the application of learning strategies based on Multiple Intelligences in Islamic Religious Education at SD Negeri 13 Buton can improve students' understanding of teaching materials according to their respective intelligences. Linguistic, visual-spatial, kinesthetic, and interpersonal approaches have proven effective in creating more interesting, interactive, and meaningful learning. In addition, this method also helps develop communication skills, creativity, and social and religious values ​​in everyday life, so that students not only understand Islamic concepts in theory, but are also able to apply them in practice.